-.4f+2=.2f+11

Simple and best practice solution for -.4f+2=.2f+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.4f+2=.2f+11 equation:


Simplifying
-0.4f + 2 = 0.2f + 11

Reorder the terms:
2 + -0.4f = 0.2f + 11

Reorder the terms:
2 + -0.4f = 11 + 0.2f

Solving
2 + -0.4f = 11 + 0.2f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-0.2f' to each side of the equation.
2 + -0.4f + -0.2f = 11 + 0.2f + -0.2f

Combine like terms: -0.4f + -0.2f = -0.6f
2 + -0.6f = 11 + 0.2f + -0.2f

Combine like terms: 0.2f + -0.2f = 0.0
2 + -0.6f = 11 + 0.0
2 + -0.6f = 11

Add '-2' to each side of the equation.
2 + -2 + -0.6f = 11 + -2

Combine like terms: 2 + -2 = 0
0 + -0.6f = 11 + -2
-0.6f = 11 + -2

Combine like terms: 11 + -2 = 9
-0.6f = 9

Divide each side by '-0.6'.
f = -15

Simplifying
f = -15

See similar equations:

| 6x^3-x^2-5x=0 | | 90=1500*r*2 | | y=41/11(88)+128/11 | | 4x-6=3x+6 | | .25+x=-.58 | | 7(3x+6)=7-(x-2) | | 8(v+2)-4v=2(2v+1)-4 | | y=41/11(20)+128/11 | | -6m-6+8m=-5m-5+2m-1 | | y=41/11(18)+128/11 | | 3=4p+8-3p | | -30=5r | | (y-4)(3-7)=.25 | | 3c+5=2c+2 | | 67x-34+2=5 | | 8(v+2)-4v+7=8v+7 | | 3+(56+x)=34 | | 21j-12=14j+37 | | -6y+14+14y=32 | | 7=-d+13 | | -21.2=p-12.7 | | .333h-4(.666h-3)=.666h-6 | | 8-5n=-7 | | 18a^6-25a^5+8a^4=0 | | 4n+12=2 | | 4x-2/3=x+2 | | 4s-1=8-2a | | -(3x-5)=2 | | 35y^4-205y^3+150y^2=0 | | y-7=-4x-4 | | (9y^2)-12y+1=0 | | 2x^4-24x^3+54x^2=0 |

Equations solver categories